Implementation of PSAK No. 45 at the Education Foundation in Semarang in the Theory of Planned Behavior Perspective - Fariztian, Anies; Wahyudin, Agus; Khafid, Muhammad (Journal of Economic Education, 2018)
Implementation of PSAK No. 45 is the standard for preparing financial statements for non-profit organizations. This study aims to determine the implementation of PSAK No. 45 on educational foundations in the city of Semarang by using Theory of Planned Behavior. The results of the study show that the effect of the belief variable on attitudes towards the implementation of PSAK No. 45, subjective norms, perceptions of behavior control, intention to implement PSAK No. 45 is a direct relationship that has a significant effect. the results of research on the intention of implementing PSAK No. 45 has a significant effect on the implementation behavior of PSAK No. 45. Effect of confidence in the implementation behavior of PSAK No. 45, the attitude of implementing PSAK No. 45, subjective norms and perceptions of behavioral control over intention is a direct relationship but the effect is not significant. And the influence of belief through attitudes towards the implementation of PSAK No. 45, perception of behavioral control on the intention to implement PSAK No. 45 which is an indirect relationship has no significant effect. Implementation of PSAK No. 45 is the standard for preparing financial statements for non-profit organizations. This study aims to determine the implementation of PSAK No. 45 on educational foundations in the city of Semarang by using Theory of Planned Behavior. The results of the study show that the effect of the trust variable on attitudes towards the implementation of PSAK No. 45, subjective norms, perceptions of behavior control, intention to implement PSAK No. 45 is a direct relationship that has a significant effect. the results of research on the intention of implementing PSAK No. 45 has a significant effect on the implementation behavior of PSAK No. 45. Effect of confidence in the implementation behavior of PSAK No. 45, the attitude of implementing PSAK No. 45, subjective norms and perceptions of behavioral control over intention is a direct relationship but the effect is not significant. And the influence of trust through attitudes towards the implementation of PSAK No. 45, perception of behavioral control on the intention to implement PSAK No. 45 which is an indirect relationship has no significant effect.